New narratives, new selves: Complicating addiction in online alcohol and other drug resources. (27th November 2015) - Pienaar, Kiran; Fraser, Suzanne; Kokanovic, Renata; Moore, David; Treloar, Carla; Dunlop, Adrian
Abstract: Within the expansive qualitative literature on alcohol and other drug (AOD) use, knowledge of lived experiences of AOD addiction is limited. Much of the existing scholarship reifies addiction as a calamitous state, and pathologises those believed to be experiencing it. Such research discounts the many ways people live with regular AOD use and is unable to tell us much about how addiction emerges through, rather than precedes, people's experiences and understandings of it. This article draws on the theoretical literature on the production of social problems and the concept of "ontological politics" to introduce an innovative approach to understanding lived experiences of AOD addiction. Applying this literature to a critical analysis of personal narratives from two Australian AOD websites, we demonstrate how addiction is conceived narrowly in these narratives as a disorder of compulsion, amenable to treatment. Not only does this conception reproduce unhelpful assumptions about addiction, it also reifies it as a stable, unified entity, the boundaries of which are fixed. Against this familiar account, we conceive addiction as an emergent, fiercely contested phenomenon, constituted in part through the very measures designed to treat it. This shift in focus allows an innovation in engaging with addiction, which is being pursued in a new Australian research project: the development of a public website presenting lived experiences of addiction that will be (1) a means of challenging existing public discourses, and (2) an intervention in the social production of addiction. The article concludes by considering the politics of this approach and how it might reshape addiction.